Internationalisation as mutual adjustment in the learning and teaching experiences of international students and academic staff: a case study in a Malaysian Technical University Setting - Mohd Faiz, Nur Sofurah (2014)
Research on the academic and social adjustment experiences of international students who travel to other countries to undertake formal studies in higher education has predominantly been carried out in Western countries such as the United Kingdom, United States, Australia and New Zealand. However, phenomena associated with international students in non-traditional but emerging education markets are still relatively underresearched. This doctoral research project responds to this gap in the literature by investigating a developing and unexamined aspect of internationalisation in Malaysian higher education. It investigates internationalisation at the level of learning and teaching activities through the conceptual lens of mutual adjustment—a theory that portrays the dynamism of relationships and outcomes in internationalised education settings. Mutual adjustment in this study was researched through the learning experiences of international students from the Middle East and Africa, as well as the pedagogical experiences of Malaysian academic staff at the Malaysian Technical University (MTU, a pseudonym)—a technical higher education institution that is one of the Technical and Vocational Education and Training (TVET) providers in Malaysia. MTU has been the main Malaysian TVET higher education provider to actively become involved in internationalisation activities; it has been recruiting international students since 2004. Jin‘s (1992) theory underlying the Cultural Synergy model and Biggs‘s (1996) Presage, Process and Product (3P) model were used to underpin the theoretical framework for mutual adjustment devised for this study. This framework posits that adjustment is a dynamic two-way process between international students and academic staff. A qualitative case study methodology was adopted for this study. Focus groups and indepth interviews were conducted with 11 international students and nine academic staff participants across three different engineering programs. Thematic analysis of the data revealed a complex and interrelated set of issues affecting the process of mutual adjustment; these issues affected international students, academic staff, local students and the institution more widely. While international students‘ experiences at MTU reflected many issues that have been identified in previous research on students studying overseas, the nature and characteristics of the learning and teaching environment at MTU also resulted in some novel findings—for example, the effect of English as the language of instruction on international students, academic staff and local students, who all speak English as an Additional Language (EAL). The emphasis on applied learning, which is characterised by a ‗hands-on‘ approach, affected international students in specific ways, especially those who had no previous experience in laboratory work. In addition, the practices of Islam, which were informally embedded in the educative process, significantly affected the experiences of both international students and academic staff, who all shared the same religion. While the ‗ideal‘ situation of mutual adjustment conjures up images of reciprocity, connectedness, complementarity, cooperation, partnership and positive changes for all parties involved in internationalised education settings, this research highlights a process that is far more chaotic, contested and less predictable in a setting where the institution itself is still in a relatively early stage of internationalisation. The research findings revealed that the process and outcomes of mutual adjustment in this case study were fragmented and contradictory, and they were more often characterised by high degrees of tension between international students and academic staff. This research makes a valuable contribution to the conceptualisation of internationalisation in higher education and the related body of knowledge at the level of human interactions in the classroom. It is also the first investigation to focus on the adjustment of international students in the Malaysian TVET setting and how their presence has affected and influenced the teaching practices of academic staff. As such, it has implications for institutions in Malaysia that are interested in learning more about the internationalisation of higher education.